Factors Affecting Procurement Performance in the Case of Awassa Textile Share Company (Global Journal of Management and Business Research, 2016)
The main objective of the study was to assess factors affecting procurement performance in Awassa Textile Share Company. The study was conducted to examine the impacts of staff competency, procurement procedure and resource allocation on procurement performance. Descriptive research design was used in executing the study. The targeted group of the study was top level managers, middle level managers and procurement staffs who are pertinent to the process, function and decision making of procurement. These were the entire group of interest for study consisting 40 employees. Accordingly, the sampling technique was purposive sampling. Primary data was collected using questionnaire. Descriptive and inferential data analysis methods were used. All respondents filled in and returned the questionnaire, making the response rate 100%.
Keywords: procurement performance; staff competency; procurement procedure and resource allocation on procurement